Perencanaan lokasi mini sabodam untuk pengendalian sedimentasi pada Calon Waduk Ciawi, DAS Ciliwung, Indonesia - Santosa Sandy Putra; Soewarno Soewarno; Dwi Kristianto (JURNAL SUMBER DAYA AIR, 2017)
Sediment management in The Upstream Ciliwung Watershed is a key to the maximum storage function achievement of The Proposed Ciawi Reservoir. The sediment that is potentially decrease the reservoir storage can be detained before it enters the reservoir by the mini sabodam construction. The small storage capacity of the mini sabodam makes the structure easy to be build. Moreover, mini sabodam does not extremely change river beds profile so that the river biota can still migrate from the downstream to upstream. This research was focused on the proposed location of the mini sabodam mapping in The Upstream Ciliwung Watershed based on sediment balance analysis in the watershed. The sediment balance analysis in the watershed was simulated by Soil and Water Assessment Tool (SWAT) numeric model, which were based on the slope condition, the soil physical characteristics, and the land cover. The Upstream Ciliwung area was classified into several HRU (Hydrological Response Unit). Each of them represents the area response to any rain event. After passing through the validation process, the model was used for measuring the sedimentation rate at the projected mini sabodam location. This research resulted technical frameworks related to the arrangement, the storage capacity, and the sediment dredging scenarios of the mini sabodam that must be conducted by communities and the river authority. The final results of this research are technical references toward the Proposed Ciawi Reservoir sedimentation control masterplan improvement.